The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3390/ijerph14020175
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Environment and Falls among Community-Dwelling Older Adults

Abstract: Background: Falls present a major challenge to active aging, but the relationship between neighborhood factors and falls is poorly understood. This study examined the relationship between fall events and neighborhood factors, including neighborhood social cohesion (sense of belonging, trust, friendliness, and helpfulness) and physical environment (vandalism/graffiti, rubbish, vacant/deserted houses, and perceived safety walking home at night). Methods: Data were analyzed from 9259 participants over four bienni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 56 publications
4
38
0
3
Order By: Relevance
“…Subgroup analysis suggested that being a woman may be a risk factor for falling, corroborating literature reports 77,78 . The results revealed that women are 60% more likely to fall than men.…”
Section: Discussionsupporting
confidence: 85%
“…Subgroup analysis suggested that being a woman may be a risk factor for falling, corroborating literature reports 77,78 . The results revealed that women are 60% more likely to fall than men.…”
Section: Discussionsupporting
confidence: 85%
“…This focus may reflect the significant preventable burden both transport-related injury 49 and excess weight 50 place on the Canadian healthcare system. Despite some evidence elsewhere showing relations between the urban form or built environment and falls in the older adult population, 20,21 this evidence appears to be scant within the Canadian context. There is a recognized need for evidence in relation to the impact of urban form on the health of older Canadian adults, including the enablers and barriers to 'aging in place'.…”
Section: Discussionmentioning
confidence: 97%
“…Systematic review findings, which are often based on a synthesis of studies from multiples countries, provide some evidence for associations between a variety of built environment features (e.g., food environment, walkability, greenery) and weight status, 14,15 blood pressure, 15 metabolic syndrome, 15 diabetes, 15,16 and major cardiovascular outcomes such as myocardial infarctions, coronary heart disease, congestive heart failure and stroke. 15 Further, built environment features are associated with motor vehicle-related bicyclist (e.g., presence of bike routes, lanes, and paths) 17 or pedestrian (e.g., traffic-calming infrastructure and roadway design) 18,19 injuries among adults, and associated with the risk of outdoor falls and fall-related injuries in older adults (e.g., perceived personal safety and neighbourhood disorder 20,21 and sidewalk quality 21 ). In addition to associations with physical health, evidence also suggests that built environment features are associated with mental health (e.g., depression, anxiety, and distress) 11,22 and intervening variables such as stress, social support and social capital.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the functional impairment and loss of abilities, mobility, and activity, the areas of older adults decrease significantly, usually not far beyond their neighborhood [7]. Compared with the younger group, older adults spend more time in their neighborhood environment for social, recreational, and task-related activities [8]. Consequently, it is essential to improve the neighborhood environment to enhance the quality of life (QoL) of community-dwelling older adults.…”
Section: Introductionmentioning
confidence: 99%